Eating‐related distress and need for nutritional support of families of advanced cancer patients: a nationwide survey of bereaved family members. Issue 5 (15th February 2016) - Amano, Koji; Maeda, Isseki; Morita, Tatsuya; Okajima, Yoshiro; Hama, Takashi; Aoyama, Maho; Kizawa, Yoshiyuki; Tsuneto, Satoru; Shima, Yasuo; Miyashita, Mitsunori
Abstract: Background: A number of advanced cancer patients are suffering from physical and psychosocial burdens because of cancer cachexia, and these burdens also greatly impact on their family members and relationships between patients and family members. It is necessary to consider the psychosocial impact of cancer cachexia on family members of advanced cancer patients. Methods: A cross‐sectional anonymous nationwide survey was conducted involving 925 bereaved family members of cancer patients who had been admitted to 133 inpatient hospices throughout Japan. Results: A total of 702 bereaved family members returned the questionnaires (response rate, 75.9%). Concerning eating‐related distress, 'I served what the patient wanted without consideration of calories and nutritional composition' was highest (75.1%), and 'I tried making many kinds of meals for the patient' and 'I was concerned about planning meals for the patient every day' followed (63.0% and 59.4%, respectively). The top 5 of the 19 items were categorized as 'fighting back'. Need for nutritional support was high (72.2%), and need for explanations about the reasons for anorexia and weight loss of patients was moderate (41.4%). Explanatory factor analysis of eating‐related distress identified the following four domains: (factor 1) feeling that family members forced the patient to eat to avoid death, (factor 2) feeling that family members made great efforts to help the patient eat, (factor 3) feeling that eating was a cause of conflicts between the patient and family members, and (factor 4) feeling that correct information was insufficient. Results of multiple logistic regression analysis showed that spouse, fair/poor mental status, factors 1, and 4 were identified as independent determinants of major depression {odds ratio [OR] 3.27 [95% confidence interval (CI) 1.24–8.60], P  = 0.02; OR 4.50 [95% CI 2.46–8.25], P  < 0.001; OR 2.51 [95% CI 1.16–5.45], P  = 0.02; OR 2.33 [95% CI 1.13–4.80], P  = 0.02, respectively}. Conclusions: A number of family members of advanced cancer patients experienced high levels of eating‐related distress and had a need for nutritional support.